THE EFFECT OF FUN COOKING ACTIVITIES ON THE SOCIAL-EMOTIONAL DEVELOPMENT OF CHILDREN AGED 5-6 YEARS AT PKK KINDERGARTEN PONTIANAK - Shalini, Tiara; Miranda, Dian; Perdina, Siska (Universitas Tanjungpura, 2025)
This study aims to determine the influence of fun cooking activities on the social-emotional development of children aged 5-6 years in Pontianak City PKK Kindergarten. This study uses a quantitative method of experimental form with a pre-experimental research design of one group pretest-postest. The number of samples in this study is 30 children. The data collection technique in this study uses observation sheets, checklist lists and documentation. The results of the study showed a significant increase in children's social-emotional development after doing fun cooking activities, shown in the results of the t-test (t-count = 27,707; significance 0.000 < 0.05). Interesting fun cooking activities, combined with food that children like, and support from teachers, fun cooking activities have proven to be effective in improving children's social-emotional development.